Analisis Etika Bisnis dan Strategi Korporasi dalam Kasus Penyitaan Dana (2025) - Adam Saputro; Halimah Zahrah; Ahmad Naufal Ramadhan; Faishal Bahrul Ulum (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the crisis communication strategy employed by PT Wilmar Nabati Indonesia in response to the seizure of IDR 11.8 trillion by the Attorney General's Office of the Republic of Indonesia in 2025. In this case, a narrative conflict emerged between Wilmar, which claimed the funds were a form of “voluntary guarantee,” and the Attorney General’s Office, which asserted the funds were “evidence of a criminal act of corruption.” This research uses a qualitative approach with a single case study method and employs discourse analysis and framing analysis on official documents, media reports, and expert commentary. Data were analyzed using the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Wilmar’s communication framing tends to mislead the public due to the absence of legal clarity. This framing contradicts key principles of business ethics, such as honesty, transparency, and social responsibility, and violates the fundamental standards of Good Corporate Governance (GCG). The lack of synchronization between the company’s legal and public relations divisions indicates weak internal coordination in managing legal crises. This study recommends that corporations establish integrated crisis communication systems involving legal teams and strengthen ethical and governance training for senior management. The results of this research offer a valuable contribution to the development of ethical and responsible corporate communication strategies in facing legal pressure..